Cool-associated Tyrosine-phosphorylated Protein 1 Is Required for the Anchorage-independent Growth of Cervical Carcinoma Cells by Binding Paxillin and Promoting AKT Activation - Yoo, Sungsoo M. (J Biol Chem, 2017)
Cool-associated tyrosine-phosphorylated protein 1 (Cat-1) is a signaling scaffold as well as an ADP-ribosylation factor-GTPase-activating protein. Although best known for its role in cell migration, we recently showed that the ability of Cat-1 to bind paxillin, a major constituent of focal complexes, is also essential for the anchorage-independent growth of HeLa cervical carcinoma cells. Here we set out to learn more about the underlying mechanism by which Cat-paxillin interactions mediate this effect. We show that knocking down paxillin expression in HeLa cells promotes their ability to form colonies in soft agar, whereas ectopically expressing paxillin in these cells inhibits this transformed growth phenotype. Although knocking down Cat-1 prevents HeLa cells from forming colonies in soft agar, when paxillin is knocked down together with Cat-1, the cells are again able to undergo anchorage-independent growth. These results suggest that the requirement of Cat-1 for this hallmark of cellular transformation is coupled to its ability to bind paxillin and abrogate its actions as a negative regulator of anchorage-independent growth. We further show that knocking down Cat-1 expression in HeLa cells leads to a reduction in Akt activation, which can be reversed by knocking down paxillin. Moreover, expression of constitutively active forms of Akt1 and Akt2 restores the anchorage-independent growth capability of HeLa cells depleted of Cat-1 expression. Together, these findings highlight a novel mechanism whereby interactions between Cat-1 and its binding partner paxillin are necessary to ensure sufficient Akt activation so that cancer cells are able to grow under anchorage-independent conditions.